1981
DOI: 10.1071/ar9810203
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and nitrogen fertilizer effects on wheat. I. Concentrations of sulfur and nitrogen and the nitrogen to sulfur ratio in grain, in relation to the yield response

Abstract: Grain samples from a factorial (5 sulfur x 3 nitrogen treatments) field experiment with Olympic wheat, which showed yield responses to both factors, were analysed for total sulfur and nitrogen. Sulfur application increased the grain sulfur concentration more with high than with low nitrogen treatment, but had only small effects on the nitrogen concentration in grain. Nitrogen application increased the grain sulfur concentration at high but not low sulfur and increased grain nitrogen concentration at all sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
54
1
4

Year Published

1985
1985
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 24 publications
12
54
1
4
Order By: Relevance
“…This study also brought out that N application increases S uptake by wheat. A positive N × S interaction in wheat has been reported (Randall et al 1981;Mishra et al 2001). These results also support the contention that heavy application of nitrogen without S application has depleted soils of native S in intensive cropping systems, such as rice-wheat in Asia (Prasad 1996).…”
Section: Discussionmentioning
confidence: 96%
“…This study also brought out that N application increases S uptake by wheat. A positive N × S interaction in wheat has been reported (Randall et al 1981;Mishra et al 2001). These results also support the contention that heavy application of nitrogen without S application has depleted soils of native S in intensive cropping systems, such as rice-wheat in Asia (Prasad 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Considering the lack of consistent differences in wheat seed yield response, plus the extra accumulation of SO 4 -S in soil, and the reduced percent recovery of applied S from 20 than 10 kg S ha -1 in plant and plant + soil, the 10 kg S ha -1 rate of sulphate-S appears to be sufficient for optimum wheat yield at this site, which is lower than the 15-30 kg S ha -1 suggested for canola in the prairie provinces (Nyborg et al 1974;Nuttall et al 1987;Jackson 2000;Malhi and Gill 2002). The response of yield and quality of wheat grain was found to be associated with <1200 mg S kg -1 for total S concentration in seed (Moss et al 1981;Randall et al 1981;Randall and Wrigley 1986), which is lower than the S concentration in seed, more so in 2001 and 2002, in the present study. Similarly, 10 kg S ha -1 was considered adequate for winter barley on sandy soils in Wales and southwest England (Withers et al 1995) and for wheat in northwest USA .…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting are the results in literature on the effect of sulphur fertilization on protein content. In fact Randall et al (1981) reported that an increase in applied S may increase, decrease or have no effect on protein content, depending upon the grain S status and the N supply. Moreover, also Zhao et al (1999a) and Naeem and MacRitchie (2003), showed that sulphur availability does not alter total protein content.…”
Section: Discussionmentioning
confidence: 99%